Bonding Strength between Geopolymer Fly Ash to Ordinary Portland Cement Concretes using Mohr-Coulomb Theory - Atan, Hairiah; Othman, Nor Hazurina; A. Khalid, Nur Hafizah; Sainudin, Muhammad Shabery; Tayeh, Bassam A. (International Journal of Sustainable Construction Engineering and Technology, 2022)
This paper presents an experimental study to analyse the bonding strength between geopolymer concrete (GC) and normal concrete (NC) bond substrate. Three different strengths of GC which were 80 MPa, 85 MPa and 90 MPa were bonded to 30 MPa NC and denoted as NC30-GC80, NC30-GC85 and NC30-GC90. Slant shear and split tensile tests were conducted to investigate the bonding strength between two different substrates. The effect of bonding was then determined by using Mohr-Coulomb theory where critical bonding condition (smooth surface) was created. From the analysis, it was found that NC30-GC80 had the most powerful self-adhesion between GC towards NC. This result indicated the highest bonding strength of GC to NC at critical condition. Such strong bond was obtained by the effect of self-adhesive from GC to NC. The self-adhesive characteristic which represented by pure shear strength was obtained from Mohr-Coulomb theory.